Evaluation the Pulmonary Tuberculosis Control Program with Strategy DOTS in Puskesmas Tanah Kalikedinding Surabaya - Adistha Eka Noveyani; Santi Martini (Universitas Airlangga, 2014)
The Directly Observed Treatment, Short-course (DOTS) Strategy is a tuberculosis control program. This study aims to evaluate the implementation of the DOTS program in Public Health Center (PHC) of Tanah Kalikedinding whose results are associated with the achievement of tuberculosis indicators. This study uses a descriptive design with a population that is all lung specialist doctors, tuberculosis officers, laboratory workers, and pulmonary tuberculosis patients. Sampling technique with purposive sampling. Data collection by interview questionnaire and checklist. The variables of this study are case finding, treatment, driving and inhibiting factors, recording and reporting, and outcomes based on tuberculosis indicators. The results showed the Case Detection Rate (CDR) at 2013 was 112% meeting the national target ≥70%. This success was due to the selection of up to 87.5% in suspected tuberculosis (cough> 2 weeks) and all patients were examined according to the diagnosis flow in the guidelines of the Ministry of Health of the Republic of Indonesia, while the Success Rate (SR) at 2013 was 65.5% under the target ≥85%. This is due to the fact that there are still patients who do not have a Drug Supervisor (PMO). The reinforcing factor is routine counseling by staff at the Public health center (PHC). The inhibiting factor is the distance to the PHC which most of the patients are more than 1 km (65.6%). Recording and reporting using an electronic system and reported online. The conclusion of the study is the need for drug swallowing supervision to improve the success of the treatment is expected that all tuberculosis patients have PMO.